Upregulated Interleukin 21 Receptor Enhances Proliferation and Epithelial-Mesenchymal Transition Process in Benign Prostatic Hyperplasia - Xu, Deqiang; Chen, Ping; Xiao, He; Wang, Xinghuan; DiSanto, Michael E.; Zhang, Xinhua (Frontiers in Endocrinology, 2019)
Background: Benign prostatic hyperplasia (BPH) is a quite common urological disease in aging men. But the pathophysiology remains unclear. Many interleukins (ILs) and related chronic inflammatory markers have been suggested to play a role in the development of BPH in recent decades. As a new member of ILs family, IL-21 receptor (IL-21R) could modulate cell proliferation. However, its role has never been determined in the prostate. The current study aimed to elucidate the roles of IL-21R in the development of BPH. Material and methods: Human prostate tissues, cell lines and rats were used. The expression and localization of IL-21R were determined with quantitative real-time PCR (qRT-PCR), Western Blot, and immunohistochemistry staining. BPH-1 cells with IL-21R silenced were cultured or co-cultured with macrophages (active THP-1, AcTHP-1). Apoptosis and cell cycles were tested with Flow Cytometry and Western Blot. Epithelial-mesenchymal transition (EMT) processes were detected with Western Blot and immunofluorescent staining. In vivo, rat prostatitis concomitant with BPH model was induced through intraprostatic injection of lipopolysaccharide (LPS). Rat prostate was observed with Hematoxylin and Eosin (H & E) staining and masson’s trichrome staining. The expression and localization of IL-21R in rat prostate were also examined. Results: IL-21R was found to be highly expressed in human, as well as rat, prostate, mainly in the epithelial compartment. BPH concomitant with prostatitis significantly upregulated the expression of IL-21R. Knockdown of IL-21R induced cell apoptosis and cycle arrest at G0/G1 phase, and blocked EMT processes in BPH-1 cells. When IL-21R silenced BPH-1 cells were co-cultured with AcTHP-1 cells, these aforementioned processes and IL-21R were completely reversed. Prostatic hyperplasia was associated with IL-21R upregulation in the LPS induced prostatitic rat. Conclusions: Our novel data suggests modulated expression functional activity of IL-21R in the development of BPH. IL-21R mainly localized in prostate epithelium and it was upregulated in hyperplastic prostate tissues. IL-21R enhanced proliferation of BPH-1 cells, via inhibition of cell apoptosis and modulating cell cycles, as well as EMT processes in the case of inflammatory stimuli.